Landscapes of survival: the archaeology and epigraphy of Jordan's north-eastern desert and beyond - Akkermans, Peter M. M. G. (Sidestone Press, 2020)
The 'Black Desert' begins just south of Damascus and comprises some 40,000 km2 of dark and desolate basalt fields, which stretch from southern Syria across north-eastern Jordan and reach the sand sea of the Nefud in Saudi Arabia. The rough and highly arid terrain is often difficult to access and travel through. Despite these uninviting conditions, recent fieldwork has revealed the immense archaeological and epigraphic record of the Black Desert. This material testifies to the prominent successes achieved by indigenous nomadic peoples in exploiting the basalt range through hunting and herding across centuries and millennia.To date, there is an ever-increasing interest in the archaeology of the Black Desert. In particular, Jordan is home to a range of international research projects, and exciting new discoveries convincingly demonstrate the archaeological affluence of Jordan's desert landscape. The present volume provides a wide-ranging and up-to-date examination of the archaeology and epigraphy of the immense basalt expanse as well as comparative perspectives from other parts of the Levant and the Arabian Peninsula. This collection of papers offers detailed insights and analyses on topics ranging from mobility and landscape to developments in settlement and burial practices, as well as the role of rock art and literacy in ancient desert environments. This richly illustrated book is a significant point of reference for what is rapidly becoming a most vibrant and dynamic field of research in the Levant and Arabia.